Fatigue life prediction of cord–rubber composite structures based on progressive damage analysis. Issue 6 (19th September 2018) - Jha, Niraj Kumar; Nackenhorst, Udo
Abstract : Purpose: The purpose of this paper is to develop a progressive damage framework to predict the fatigue life of cord-reinforced rubber composite under cyclic loadings. Special attention has been paid to failure mechanisms, like cord–rubber interfacial debonding, and rubber matrix damage. Design/methodology/approach: The constitutive modeling is based on the continuum damage mechanics (CDMs) and the thermodynamics of irreversible process. The damage in rubber is described by an istropic law, whereas elasto-plastic continuum model has been proposed for cord–rubber interphase layer. The numerical framework is implemented into commercial finite element code Abaqus/Standard via user subroutine (UMAT). Findings: One of the most important findings obtained from reviewing various techniques is that meso-level fatigue damage modeling based on developed framework can simulate competitive damage scenarios, e.g. debonding, delamination or matrix failure. Originality/value: A systematic framework for predicting failure in cord-reinforced rubber composite is formulated within the context of CDMs that can also be applied for industrial components, such as tires and airsprings.